2021
DOI: 10.1002/ajpa.24237
|View full text |Cite
|
Sign up to set email alerts
|

Variability of weaning age in mountain gorillas (Gorilla beringei beringei)

Abstract: Objectives: Weaning is a key life history milestone for mammals that represents both the end of nutritional investment from the perspective of mothers and the start of complete nutritional independence for the infants. The age at weaning may vary depending on ecological, social, and demographic factors experienced by the mother and infant. Bwindi mountain gorillas live in different environmental conditions and have longer interbirth intervals than their counterparts in the Virunga Volcanoes, yet other life his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As the locomotor transition from highly arboreal to mainly terrestrial is more pronounced in mountain gorillas than western lowland gorillas, the former is used to define the age categories. Importantly, we also note that age categories above based on changes in locomotor behaviours and epiphyseal fusion are not necessarily consistent with other developmental changes documented in Virunga mountain gorillas specifically, which reach independence (e.g., weaning at ~3.5 years; Eckardt et al, 2016 ) and age at first birth (~8+ years; Williamson & Gerald‐Steklis, 2001 ) earlier than Bwindi mountain gorillas and western lowland gorillas (Robbins & Robbins, 2021 ).…”
Section: Methodsmentioning
confidence: 57%
“…As the locomotor transition from highly arboreal to mainly terrestrial is more pronounced in mountain gorillas than western lowland gorillas, the former is used to define the age categories. Importantly, we also note that age categories above based on changes in locomotor behaviours and epiphyseal fusion are not necessarily consistent with other developmental changes documented in Virunga mountain gorillas specifically, which reach independence (e.g., weaning at ~3.5 years; Eckardt et al, 2016 ) and age at first birth (~8+ years; Williamson & Gerald‐Steklis, 2001 ) earlier than Bwindi mountain gorillas and western lowland gorillas (Robbins & Robbins, 2021 ).…”
Section: Methodsmentioning
confidence: 57%
“…Such seems to be the case when mothers of species with marked sexual dimorphism invest more resources in sons than daughters because male infants are more energetically costly (Clutton-Brock et al 1985;Hewison and Gaillard 1999;Lindstrom 1999;e.g., gorillas, G. beringei : Meder 1990; Leigh and Shea 1996;Eckardt et al 2016;Robbins and Robbins 2021; sea lions, Zalophus spp. : Oftedal et al 1987;Piedrahita et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Furuichi, 1989; 2 Eckardt et al, 2016; 3 Robbins & Robbins, 2021; 4 Nowell & Fletcher, 2007; 5 Lonsdorf et al, 2020; 6 Matsumoto, 2017; 7 Bray et al, 2018; 8 Bădescu et al, 2017; 9 van Noordwijk et al, 2013; 10 Nishida et al, 2003; 11 Wittig & Boesch, 2019; 12 Wallis, 1997; 13 van Noordwijk et al, 2018; 14 Reynolds, 2005; 15 Sugiyama, 2004; 16 Colchero et al, 2021; 17 Wich et al, 2004. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the paucity of evidence for clear energetic differences, studies have reported marked differences in life history. Virunga mountain gorillas have the earliest age of weaning and shortest interbirth interval, with Bwindi mountain gorillas having comparable values to western gorillas (Eckardt et al, 2016; Nowell & Fletcher, 2007; Robbins, Gray, et al, 2009; Robbins & Robbins, 2021; Robbins, Stoinski, et al, 2009; Stoinski et al, 2013). Western gorillas have slower physical maturation and are considered to be adults at later ages than Virunga mountain gorillas (Breuer et al, 2009; Galbany et al, 2017).…”
Section: Introductionmentioning
confidence: 99%